TINGKAT PENGELOLAAN IKAN TEMBANG (Sardinella gibbosa) YANG TERTANGKAP DENGAN BAGAN TANCAP DI KABUPATEN PANGKEP - Handayani Pratiwi B; Muhammad Jamal Alwi; Danial Danial (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2020)
The success of fishing depends on sufficient knowledge of the overall behavior of the fish, which is the basis for the development of existing methods. Utilization of Fishery Potential Activities in Pangkep Regency waters still depends a lot on simple fish catching technology. One of the factors for the success of catching fish with a chart is light. Light is a tool to help collect fish to the fishing area. Toli-toli village, Tekkolabua sub-district, Pangkep district is geographically located between 04º79'07.71